Polymerization of an epoxy resin modified with azobenzene groups monitored by near-infrared spectroscopy - Fernández, Raquel (2009)
New photosensitive materials containing photochromic azobenzene moieties were synthesized. For this purpose, an epoxy resin based on diglycidyl ether of bisphenol A (DGEBA) was reacted with an azobenzene chromophore (disperse orange 3, AZ) to satisfactorily synthesize an azo‐modified prepolymer, which was then used to generate series of epoxy‐based polymers containing azo groups. Three different amines were used as hardeners, with the aim of obtaining materials with different chemical structures. Understanding the epoxy resin polymerization kinetics is essential for intelligent processing of materials. Near‐IR (NIR) spectral analysis was used to follow the polymerization kinetics. The quality of the NIR spectra enables concentrations of individual chemical species to be measured in real time. Conversion of epoxy and primary amine groups, as well as the concentration of different groups, as a function of reaction time was therefore calculated by this spectroscopic technique. Samples containing azo units were compared to the pure DGEBA/amine systems. Results showed that the azo‐prepolymer incorporation has an accelerating effect on polymerization rate.